Lexical Diversity and Sophistication in Professional Architectural Discourse: A Computational Comparison of Native and Non-native English Writing - Kargar, Aliasghar (HERMES - Journal of Language and Communication in Business, 2025)
The current study aimed to explore the lexical differences between texts authored by native and non-native English professional architects submitted to ArchDaily, the world’s most visited architecture website. The study focused on lexical diversity and sophistication indices, proved to be theoretically and operationally pertinent to L1 and L2 writing discriminations. The corpus of the study comprised randomly selected texts in the category of residential architecture as the commonest instances of architecture projects written by Iranian and British architects. As stated in the website, the texts are authored and revised by the architects themselves and are strongly advised to undergo thorough review and verification for accuracy and quality. The data underwent analysis using Cohmetrix Core Desktop Beta (2023) package, with the results subsequently input into SPSS for further analysis. Preliminary analysis revealed statistical variances between most of the diversity and sophistication indices with supplementary analysis indicating that lexical indices such as word frequency, familiarity, hypernymy, and diversity significantly contributed to discerning between native speaker (NS) and non-native speaker (NNS) compositions. The study concluded that the writing norms of NS and NNS authors within distinct professional communities may not align with the conventional proficient and non-proficient standards typically observed in language studies. The results highlight the significance of adhering to the target community's stylistic conventions, which carries important implications for instructional approaches in ESP and academic writing programs.